E-029 Mechanical Thrombectomy in Pediatric Acute Ischemic Stroke: Clinical Outcomes and Literature Review. (29th July 2016) - Madaelil, T; Kansagra, A; Derdeyn, C; Cross, D; Moran, C
Abstract : There is limited data on outcomes of mechanical thrombectomy for pediatric stroke using modern devices. In this study, we report two cases of pediatric acute ischemic stroke treated with mechanical thrombectomy, both with good angiographic result (TICI 3) and clinical outcome (no neurological deficits at 90 days). In addition, we conducted a literature review of all previously reported cases describing the use of modern thrombectomy devices. Including our two cases, the aggregate rate of partial or complete vessel recanalization was 100% (22/22), and the aggregate rate of favorable clinical outcome was 91% (20/22). This preliminary evidence suggests that mechanical thrombectomy with modern devices may be a safe and effective treatment option in pediatric patients with acute ischemic stroke. Disclosures: T. Madaelil: None. A. Kansagra: None. C. Derdeyn: None. D. Cross: None. C. Moran: 2; C; Medtronic Neurovascular.